Potential of gut-derived short-chain fatty acids to control enteric pathogens - Zhan, Ziyang; Tang, Hao; Zhang, Ying; Huang, Xinxiang; Xu, Min (Frontiers in Microbiology, 2022)
Short-chain fatty acids (SCFAs) are a very important group of metabolites located in the gut that play a crucial role in the regulation of gut function and pathogen resistance. Since many enteric pathogens respond differently to various SCFAs, substantial efforts have been made to understand the regulatory effects of SCFA types on enteric pathogens. The application of protein post-translational modifications (PTMs) in bacterial research provides a new perspective for studying the regulation of enteric pathogens by different SCFAs. Existing evidence suggests that the SCFAs acetate, propionate, and butyrate influence bacterial processes by extensively promoting the acylation of key bacterial proteins. SCFAs can also prevent the invasion of pathogenic bacteria by regulating the barrier function and immune status of the host gut. In this review, we describe the mechanisms by which different SCFAs modulate the pathogenicity of enteric pathogens from multiple perspectives. We also explore some recent findings on how enteric pathogens counteract SCFA inhibition. Lastly, we discuss the prospects and limitations of applying SCFAs to control enteric pathogens.